Finding my own way in the kitchen from maternal influence and beyond – A grounded theory study based on Brazilian women's life stories. (1st July 2020) - Mazzonetto, Ana Cláudia; Le Bourlegat, Isabelle Schroeder; Guedes dos Santos, José Luís; Spence, Michelle; Dean, Moira; Fiates, Giovanna Medeiros Rataichesck
Abstract: Mothers are frequently seen as the gatekeepers of the transmission of food-related meanings and practices to their children, but little is known about how they transmit cooking-related aspects. This study aimed to understand the intergenerational transmission of cooking-related meanings and practices using a life course perspective and a constructivist grounded theory approach to present a substantive theory. The study was carried out in southern Brazil with 27 women. The core category Finding my own way in the kitchen from maternal influence and beyond is explained by four other categories. The first three show (1) that daughters implicitly and explicitly learn the idea of cooking responsibility from their mothers; (2) that mothers influence daughters by the way they involve children in the kitchen and by the feelings they express regarding cooking and (3) that daughters learn cooking practices observing their mother's cooking, cooking together, receiving instructions and eating their mother's food. The fourth category shows that daughters recreate what they learned from the mother according to their own life trajectories, social and historical context, and the people they interact with. Some of what they recreate is now part of their mothers' lives, resulting in a bidirectional influence. Strategies designed to encourage cooking need to challenge the view that the activity is solely a woman's responsibility, as well as communicate to the parents that their influence goes beyond transmitting cooking practices, as the attitudes and feelings they express towards cooking are also transferred.